Polyenylphosphatidylcholine alleviates cardiorenal fibrosis, injury and dysfunction in spontaneously hypertensive rats by regulating Plpp3 signaling - Zhang, Yongqiao; Ma, Jiayi; Wei, Feng; Gong, Jiaxin; Zhuang, Li; Zhang, Ningzhi; Cui, Zhaoqiang (Frontiers in Cardiovascular Medicine, 2024)
Objective Polyenylphosphatidylcholine (PPC), a significant therapeutic agent for liver repair, exhibits potent antioxidant and anti-inflammatory properties. Nonetheless, its impact on hypertension and hypertensive vascular diseases requires clarification. Our objective was to elucidate the protective role and mechanism of PPC in a spontaneously hypertensive rat model. Materials and methods Male WKY and SHRs were randomly assigned to four groups: WKY control, SHRs control, SHRs treated with Telmisartan (SHR-TS), and SHRs treated with PPC (SHR-PPC). Blood pressure was monitored biweekly during the treatment. Histological analyses assessed aortic vascular remodeling and cardiac and renal injuries. RNA-seq was performed on vascular smooth muscle cells (VSMCs) isolated from WKY or SHRs, and protein levels of target genes were quantified using Western blotting. Results In a dose-dependent screening test, we confirmed that PPC (200 mg/kg/day) effectively reduced blood pressure in SHRs. Treatment with PPC also mitigated cardiac and renal injury in SHRs by attenuating hypertrophy and fibrosis. Compared to WKY rats, SHRs exhibited increased intima thickness, reduced vascular tone, and heightened aortic fibrosis; however, PPC treatment significantly reversed vascular remodeling. Analysis of RNA-seq data revealed that downregulated genes were enriched in inflammation and oxidative stress pathways based on GO and KEGG enrichment analyses. PPC markedly inhibited genes such as Rela, Relb, Nfkb2, and others involved in the NF-κB pathway. Given PPC's influence on glycerophospholipid synthesis and metabolism, and its role in NF-κB-mediated transcription affecting oxidative stress and inflammation, changes in the PLAs, PLPs, and PLPPs families were analyzed in PPC-treated VSMCs. Among these, PPC notably inhibited Plpp3. Importantly, overexpression of Plpp3 significantly reversed the protective effects of PPC on hypertension-related cardiac and renal injuries, vascular fibrosis, remodeling, and tension. Conclusion We identified a new protective role for PPC in mitigating cardiac and renal injuries associated with hypertension, as well as in preventing aortic fibrosis and remodeling. Targeting the NF-κB/Plpp3 pathway may offer a promising therapeutic strategy for treating vascular diseases related to hypertension.